Penerapan Media Gambar Kartun dalam Pembelajaran Kosa Kata Bahasa Arab di Madrasah Ibtidaiyah - Mawarti, Marinten; Nurrokhmatulloh, Nurrokhmatulloh; Taubah, Miftachul (Study Program of Arabic Language Teaching, 2025)
This study analyzes the use of cartoon image media in teaching Arabic vocabulary (mufradat) to fourth-grade students at MI Mambaul Khoir Talang Prigen Pasuruan. Qualitative research with case study type Research data in the form of cartoon images in Arabic vocabulary Data collection techniques through observation, interviews, and documentation Data analysis was carried out through data reduction, data presentation, and conclusion drawing; the study finds that cartoon images significantly enhance students' motivation, memorization, and understanding of word meanings. This media fosters an interactive, engaging classroom environment, increasing participation and confidence in vocabulary usage. Supporting factors include visual appeal and the ability to simplify abstract concepts, although challenges such as limited resources and varied student abilities persist. The study suggests combining cartoon media with language games, group discussions, and creative tasks to optimize effectiveness. Future developments may involve integrating digital technologies to improve further Arabic language learning at the madrasah ibtidaiyah level.